Development and optimization of high-throughput methods to measure Plasmodium falciparum-specific growth inhibitory antibodies. - Persson, K; Lee, C; Marsh, K; Beeson, J (2006)
Antibodies that inhibit replication of Plasmodium falciparum in erythrocytes are thought to be important both in acquired immunity to malaria and as mediators of immunity generated by candidate blood-stage vaccines. However, several constraints have limited the study of these functional antibodies in population studies and vaccine trials. We report the development and optimization of high-throughput growth inhibition assays with improved sensitivity that use minimal volumes of test serum. The major inhibitory activity of serum from exposed donors was antibody mediated, but nonspecific inhibitory factors were found in untreated serum. Culture volumes could be effectively reduced to 25 microl to limit amounts of test serum or inhibitors used in assays. Performing inhibition assays over two cycles of parasite replication gave greater sensitivity than single-cycle assays, and a simple two-cycle inhibition assay was developed that yielded highly reproducible results. Determination of parasite growth by flow cytometry was most suitable for high-throughput assays using small culture volumes and was more sensitive than parasite lactate dehydrogenase assays and less prone to error and variation than microscopy. We evaluated and optimized methods to remove antimalarials and nonspecific inhibitory factors from serum that are suitable for use with small volumes of samples that are typically obtained from clinical studies. Both microdialysis and immunoglobulin purification by ammonium sulfate precipitation were effective and practical. These methods should facilitate evaluation of vaccine trials and clinical studies of immunity and are also suitable for testing drugs and other compounds for antimalarial activity.